MEMBANGUN BUDAYA HUKUM PANCASILA DI ERA REFORMASI - Junaedi; Diki Dikrurahman (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Pancasila is the result of the crystallization of the noble values of diverse Indonesian society. So that Pancasila is the ideology that brings that plurality for the sake of creating unity and unity of the nation. Moving on from that problem, Pancasila is the basis for various development of legal values, or more precisely Pancasila is used as a legal principle in building the life of society, nation and state. Therefore, the development of a legal culture will be very important to create a just and civilized Indonesian human development. With the establishment of Pancasila as a legal principle, building a legal culture must be aligned with the noble values of Pancasila as the basis of ethics and morality. Legal culture is a legal identity that can enforce the law to create social justice for all Indonesian people.